Effects of Elevated CO2 and Increased N Fertilization on Plant Secondary Metabolites and Chewing Insect Fitness - Xu, Huaping; Xie, Haicui; Wu, Shengyong; Wang, Zhenying; He, Kanglai (Frontiers in Plant Science, 2019)
Elevated atmospheric CO2 (eCO2) and increased nitrogen (N) fertilization significantly change the nutritional quality of plants and influence the growth and development of insects. However, little is known about plant metabolism and plant-insect interactions under eCO2 and increased N fertilization, especially C4 plants. Thus, the combined effects of eCO2 and increased N fertilization on maize-Ostrinia furnacalis interactions were tested in this study. Our data demonstrated that both eCO2 and increased N fertilization increased and starch content, while increased N fertilization promoted the N content in maize. The combined effects of eCO2 and increased N fertilization did not influenced thetotal non-structural carbohydrates (TNC):N ratio in maize. The jasmonic acid level of maize was enhanced by increased N fertilization and O. furnacalis infestation. The total phenolics content and defensive enzyme activities of maize increased under eCO2, increased N fertilization and O. furnacalis infestation. Protective enzyme activities were enhanced, while digestive enzyme activities, mean relative growth rate, body mass and efficiency of conversion of ingested food decreased for O. furnacalis feeding on maize grown under eCO2 and increased N fertilization. Therefore, eCO2 and increased N fertilization increased starch and N accumulation, and did not influence the TNC:N ratio, however promoted the resistance related secondary metabolites (with or without O. furnacalis induced) of maize, which ultimately decreased the fitness of O. furnacalis to the host. These results will help to better understand the metabolic mechanisms of plants and the plant-insect interaction under eCO2 and increased N fertilization in the context of future climate change scenarios.